Systematic position of Bombyx incomposita (Lepidoptera: Bombycidae), with notes on its immature biology and hostplant association - Lin, Rung-Juen; Lin, Yu-Chi; Hsu, Yu-Feng (Zootaxa, 2021)
The immature stages, morphology, and systematic position of Bombyx incomposita (van Eecke, 1929) are reported. The morphology of larva was investigated using scanning electron microscopy, and the phylogeny was inferred using six genes (COI, CAD, EF-1α, GAPDH, RpS5, and wgl). The molecular phylogeny strongly supported that B. incomposita is sister to B. huttoni Westwood, 1847. The divergence of the COI barcode, phylogenetic reconstruction, and difference in immature stages support the current classification, in which the species incomposita belongs to the genus Bombyx. We give illustrations of male and female genitalia and briefly discuss the utility of the chaetotaxy of the first instar larvae on taxonomy of silkmoths. The SV group bears six setae in B. mandarina, but eight in B. incomposita. The L1 bears three setae in Rotunda, but just single seta in Bombyx.